Environmental impact assessment handbook : a practical guide for planners, developers and communities. - Carroll, Barbara, 1950-; Fothergill, Josh; Murphy, Jo; Turpin, Trevor (ICE Publishing, 2019)
Explaining the EIA process and legal procedures in a clear and straightforward way, the authors employ their extensive practical experience to cover each of the steps and associated studies needed to undertake an EIA and to produce a successful environmental statement. Environmental Impact Assessment Handbook is fully updated in line with EU legislation for ensuring protection of the environment from new development, including the 2014 EU directive transposed into UK law in 2017, which heralds a step-change in scope and approach.
Previous edition issued in print: 2009.
Keywords: Environmental impact analysis -- Great Britain.; Environmental impact analysis -- Law and legislation -- Great Britain.; elektronické knihy; electronic books